2020
DOI: 10.1177/1756284820927282
|View full text |Cite
|
Sign up to set email alerts
|

Orodispersible budesonide tablets for the treatment of eosinophilic esophagitis: a review of the latest evidence

Abstract: Eosinophilic esophagitis (EoE) is a chronic inflammatory disorder of the esophagus characterized by symptoms of esophageal dysfunction and eosinophil-predominant inflammation. The incidence of EoE has increased substantially over the past two decades in Europe and North America. The natural course of EoE appears to be progressive with a high risk of stricture formation. The current European guideline recommend swallowed topical corticosteroids, proton-pump inhibitors or dietary intervention for initial and lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 52 publications
0
33
0
6
Order By: Relevance
“…21 Heterogeneity between study designs, response criteria, and results has led to challenges comparing efficacy end points and reproducing outcomes between maintenance studies. 22 Budesonide orodispersible tablet (BOT; 1.0 mg twice daily) has been evaluated vs placebo for maintaining remission in adults with EoE (48 weeks). 18 In the BOT trial, 75% of patients reported persistent remission vs 4% of placebo-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…21 Heterogeneity between study designs, response criteria, and results has led to challenges comparing efficacy end points and reproducing outcomes between maintenance studies. 22 Budesonide orodispersible tablet (BOT; 1.0 mg twice daily) has been evaluated vs placebo for maintaining remission in adults with EoE (48 weeks). 18 In the BOT trial, 75% of patients reported persistent remission vs 4% of placebo-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study was conducted on 159 morbidly obese patients on vertical gastroplasty before and after the endoscopy. About 31% of patients had visible EE on endoscopy 22 . Another study found 53 and 35 patients with gastritis and reflux respectively while carrying their study on a total of 104 gastro esophageal patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bei insgesamt sehr guter Verträglichkeit wurde in den Kontrollendoskopien bei weniger als 10 % der Patienten eine geringgradige lokale Candidiasis beobachtet, die lokal behandelt wurde und in keinem Fall zu einem Abbruch der lokalen Steroidtherapie führte [22,25]. Die konsistent hohe Wirksamkeit der orodispersiblen Budesonid-Tablette erklärt sich möglicherweise durch die ösophagus-spezifische Darreichungsform, bei der das im Speichel aufgelöste Budesonid schrittweise geschluckt in das Zielorgan gelangt, und aufgrund der mukoadhäsiven Eigenschaften des Speichels mutmaßlich eine verlängerte Exposition des Wirkstoffs auf der Ösophagusschleimhaut erreicht wird [29]. Schließlich wurde in zwei aktuellen Metaanalysen die hohe Effektivität der orodispersiblen Budesonid-Tablette in der Remissionsinduktion der EoE unterstrichen [18,30].…”
Section: Orodispersible Budesonid-tabletteunclassified